Anthropometric indicators as predictors of dynapenia in postmenopausal women - Lucas dos Santos; Camille Giehl Martins Miranda; Italo Emmanoel Silva e Silva; Patrícia Honório Silva Santos; Thaís Alves Brito; Marcos Henrique Fernandes; José Ailton Oliveira Carneiro (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: Anthropometry represents an alternative to the evaluation of nutritional status and screening of events related to muscle fitness. Therefore, this study aimed to compare anthropometric indicators of postmenopausal women with and without dynapenia and to identify the predictive capacity of these indicators to screen the respective outcome in this population. Methods: Cross-sectional epidemiological study, conducted with postmenopausal women. Dynapenia was diagnosed by handgrip strength < 20 kgf. Arm (AC), abdominal (AbC), hip (HC) and calf circumferences (CC), triceps, biceps, subscapular, supraspinatus and thigh skinfolds were analyzed. Body Mass Index, Conicity Index (CI), Body Adiposity Index (BAI), Waist to Hip and Waist to Height Ratio (WHtR), Corrected Arm Muscle Area (CAMA) and Arm Muscle Circumference (AMC) were calculated. Results: A total of 273 women participated in the study. The BAI, WHtR, and CI did not present significant differences between the groups. For the other indicators, the dynapenic group obtained significantly lower values compared to the non-dynapenic. AC was the indicator with the highest sensitivity to screen for postmenopausal dynapenia (79.8%). While CAMA and AMC were the indicators with the best specificity (86.2%). However, CC showed the best balance between sensitivity (67.5%) and specificity (63.0%). Conclusion: The indicators AC, CAMA, and/or the AMC can be used together, or CC alone, to predict postmenopausal women with dynapenia. Therefore, these indicators can be used as important epidemiological tools to improve women's health surveillance actions.